Pemanfaatan Pelatihan Pembuatan Sabun Cuci Piring di Desa Pidodowetan Sebagai Upaya Pemberdayaan Masyarakat dan Kemandirian Ekonomi - Nada Saniyah; Ellyzena Wulandari; Serli Sanggang Sarasta; Muhammad Hanafi; Mudzakir Nur Hidayatussani; Nur Luthfi Hanif Al-Baihaqi; Ahmad Shohibul Wafa; Fenny Bintarawati (Lembaga Pengembangan Kinerja Dosen, 2024)
Dish soap is a basic necessity whose demand continues to increase. Dish soap making training has proven to be an effective effort in empowering communities, especially women, and encouraging economic independence. This activity not only transfers new knowledge and skills, but also opens up sustainable business opportunities. By utilizing local ingredients, the community can produce quality dish soap at a more affordable cost. By producing their own, the community not only saves expenses, but also has full control over the quality of the products produced. In addition, this dish soap making training can also strengthen solidarity and increase the added value of local products.